2012
DOI: 10.1111/j.1349-7006.2012.02202.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological evaluation of personalized peptide vaccination in refractory small cell lung cancer

Abstract: Since the prognosis of small cell lung cancer (SCLC) remains poor, development of new therapeutic approaches, including immunotherapies, would be desirable. In the current study, to evaluate immunological responses in refractory SCLC patients, we conducted a small scale phase II clinical trial of personalized peptide vaccination (PPV), in which vaccine antigens are selected based on pre-existing host immunity. Ten refractory SCLC patients, who had failed to respond to chemo-and/or chemoradiotherapies (median n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 22 publications
3
37
0
Order By: Relevance
“…As a result, plasma SAA and CRP levels were inversely correlated with OS. These results were expected based on our previous study on PPV (10). These biomarkers are suggested to be important not only in cancer vaccines, but also in other treatment modalities for advanced pancreatic cancers.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…As a result, plasma SAA and CRP levels were inversely correlated with OS. These results were expected based on our previous study on PPV (10). These biomarkers are suggested to be important not only in cancer vaccines, but also in other treatment modalities for advanced pancreatic cancers.…”
Section: Discussionsupporting
confidence: 73%
“…Patients pathologically and/or clinically diagnosed with pancreatic cancer were eligible for inclusion in the present study, when they had failed at least first-line chemotherapy and showed positive IgG responses to at least 2 of the 31 different vaccine candidate peptides as previously reported (10 The peptides for vaccination to individual patients were selected in consideration of the pre-existing host immunity before vaccination, by assessing the titers of IgG specific to each of the 31 different vaccine candidates (10). A maximum of 4 peptides (3 mg/each peptide), which were selected based on the results of HLA typing and peptide-specific IgG titers, in complex with incomplete Freund's adjuvant (Montanide ISA 51; Seppic, Paris, France) were subcutaneously administered once a week for 6 consecutive weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were subcutaneously injected weekly or bi-weekly with ISA51VG along with ≤4 peptides selected from the 31 peptide candidates. Clinical studies of small cell and non-small cell lung cancers have indicated that PPV does not cause severe side effects but demonstrates potential immunological efficacy to some extent (8,9). However, only a proportion of patients experience clinical benefits from such vaccines.…”
Section: Introductionmentioning
confidence: 99%